2005
DOI: 10.1093/jn/135.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Enterolignans in Healthy Men and Women Consuming a Single Dose of Secoisolariciresinol Diglucoside

Abstract: High concentrations of enterolignans in plasma are associated with a lower risk of acute coronary events. However, little is known about the absorption and excretion of enterolignans. The pharmacokinetic parameters and urinary excretion of enterodiol and enterolactone were evaluated after consumption of their purified plant precursor, secoisolariciresinol diglucoside (SDG). Twelve healthy volunteers ingested a single dose of purified SDG (1.31 micromol/kg body wt). Enterolignans appeared in plasma 8-10 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(149 citation statements)
references
References 46 publications
9
131
2
7
Order By: Relevance
“…The concentration of enterolignans in plasma is not dependent on memory, and takes into account metabolism by the colonic flora and bioavailability as well. Enterolignans will accumulate in plasma when consumed twice or thrice a day (39). Thus, steady state plasma concentrations of enterodiol and enterolactone are likely to be achieved because plant lignans are present in many foods and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of enterolignans in plasma is not dependent on memory, and takes into account metabolism by the colonic flora and bioavailability as well. Enterolignans will accumulate in plasma when consumed twice or thrice a day (39). Thus, steady state plasma concentrations of enterodiol and enterolactone are likely to be achieved because plant lignans are present in many foods and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of conversion of plant lignan precursors to END and ENL in 24-h incubations with human fecal inocula varied greatly depending on the compound and ranged from 0 to 100%. Studies have reported that urinary excretion of ENL is very low or nonexistent in some study participants challenged with SDG [9,35,36]; these results suggest that there may a subpopulation of individuals that lacks the bacteria or appropriate intestinal environment necessary for oxidation of END to ENL.…”
Section: Phytochemical Metabolism By Gut Bacteriamentioning
confidence: 94%
“…Circulating concentrations of phytochemicals, such as psoralens, lignans, and the flavonoids naringenin and hesperitin, can vary widely among individuals even in the context of controlled feeding studies [8][9][10]. The process of phytochemical disposition, like that of disposition of drugs and other xenobiotics, involves absorption, metabolism, distribution, and excretion, and each of these parts may contribute to pharmacokinetic variability (Figure 1) [11].…”
Section: Sources Of Variation In Phytochemical Metabolism and Disposimentioning
confidence: 99%
“…A Lineweaver-Burke plot gave parallel lines, a pattern consistent with uncompetitive inhibition (not shown). SDG (and SECO) is often referred to as the precursor for the enterolignans, ED and EL (Thompson et al, 1991;Borriello et al, 1985a;Kuijsten et al, 2005;Axelson et al, 1982c;Bambagiotti-Alberti et al, 1994). Much of the putative health benefits of flaxseed lignans are ascribed to the enterolignan forms, although definitive data for such assertions is lacking.…”
Section: Reversible Inhibition Of Cytochrome P450 Enzymesmentioning
confidence: 99%